Dialektika Agama dalam Komunikasi Politik Menjelang Pilpres Tahun 2024 - Khumaedi, Teddy (Lisyabab : Jurnal Studi Islam dan Sosial, 2024)
Religion is divine guidance revealed to humans to achieve happiness in their lives. Religion is a source of reference for its adherents in all their actions. As a source of values ​​and ethics, religion requires its adherents to adhere to all existing values ​​as worship. The study of religious dialectics in political communication is an ongoing theme in the trajectory of human history in various parts of the world, including in countries where the majority of the population is Muslim, such as Indonesia. This research confirms historically that political change is closely related to the dynamic context of the development of Muslims both in terms of thought and social movements. The implication is that all products of thought are not value-free. Islam has a holistic insight that provides basic principles for solving problems in human life, both in building relationships with oneself, relationships with other people, relationships with the environment, and relationships with God. In other words, Islam can be seen as a set of teachings that regulate all aspects of human life, whether economic, social, political, cultural, etc. every religious interpretation to become part of society’s legal preferences. The aim of this research is to show that exclusive and inclusive concepts are ways to respond to the reality of religion in political communication. Their influence on changes in the choice of presidential and vice presidential candidates cannot be mutually exclusive, but is understood dialectically. The phenomenon of religious dialectics in political communication, especially ahead of the 2024 presidential and vice presidential (capres-cawapres) general elections, is the core focus of this research. With the aim of opening a new veil regarding why religious dialectics is always present in political communication before every presidential election event.